2014
DOI: 10.1016/j.matbio.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Integrins and chondrocyte–matrix interactions in articular cartilage

Abstract: The integrin family of cell adhesion receptors plays a major role in mediating interactions between cells and the extracellular matrix. Normal adult articular chondrocytes express α1β1, α3β1, α5β1, α10β1, αVβ1, αVβ3, and αVβ5 integrins, while chondrocytes from osteoarthritic tissue also express α2β1, α4β1, α6β1. These integrins bind a host of cartilage extracellular matrix (ECM) proteins, most notably fibronectin and collagen types II and VI, which provide signals that regulate cell proliferation, survival, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
197
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(204 citation statements)
references
References 73 publications
3
197
1
3
Order By: Relevance
“…3 for α2β1-integrin. In conclusion, these results confirm and extend previous observations [24,[39][40][41] that monomolecular cartilage collagens were good binding substrates for all collagen-binding integrins expressed by chondrocytes.…”
Section: Binding Of Soluble Integrins To Collagens II Ix and Xisupporting
confidence: 91%
See 2 more Smart Citations
“…3 for α2β1-integrin. In conclusion, these results confirm and extend previous observations [24,[39][40][41] that monomolecular cartilage collagens were good binding substrates for all collagen-binding integrins expressed by chondrocytes.…”
Section: Binding Of Soluble Integrins To Collagens II Ix and Xisupporting
confidence: 91%
“…In agreement with this notion, we presented evidence here that the mostly non-collagenous components of collagen-containing fibrils in cartilage contain the relevant binding sites for integrins. Molecular candidates include collagen VI and microfibrils containing collagen VI [24], matrilins [11], COMP (thrombospondin 5) [13], and several SLRPs (decorin, fibromodulin, lumican) [44]. Many of these macromolecules have been associated also with a biomechanical role in cartilage (for review see [12]).…”
Section: Binding Of α1-or α2-integrin I-domains To Authentic Cartilagmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that some chondrocytes do not have the ability to migrate to damaged areas. Decrease in cell adhesion to fibronectin could be related to presence of apoptotic or necrotic chondrocytes in affected cartilage (22). Mesenchymal stem cells have the potential of differentiating into chondrocytes and can migrate to injured areas (23).…”
Section: Discussionmentioning
confidence: 99%
“…These forces are transmitted to 20 the ECM through trans-membrane receptors of the integrin family placed on the cell membrane [9], which serve as traction points over which the cell moves as well as sources of migration-related regulatory signals [1,10,11,12]. These integrins are bound to the actin filaments in the cytoskeleton through a clutch of proteins that include talin, α-actinin, vinculin and paxilin [13,3,14].…”
Section: Introductionmentioning
confidence: 99%